Clima escolar em uma escola do programa de ensino integral do estado de São Paulo - Oliveira, Maria Eduarda (Universidade Federal de São Carlos, 2026)
This dissertation was developed within the scope of the Graduate Program in Education at the Federal University of São Carlos (PPGE-UFSCar) and the Study and Research Group on School Organization: Democracy, Human Rights, and Principals’ Development (Deforges). The research on which it is based is part of a broader investigation, developed by this research group, which focused on the study of leadership and school climate in some schools that joined the São Paulo State Comprehensive Education Program (PEI) in the city of São Carlos, SP. Thus, this research constitutes a continuation of a previous one, which, among other procedures, included the application of the school climate pre-test (Moro, 2020) in one of these schools. Thus, the objective of this master's research was to map the school climate at this school, to understand its characteristics and what changes it has undergone over the last two years, marked by a change in government that had a strong impact on the state education system, particularly in PEI schools. The question posed was: what have been the changes in the school climate over the past two years? Given this objective and research question, this investigation was conducted using mixed methods (Creswell; Creswell, 2021). The administration of the school climate post-test (Moro, 2020) provided quantitative data that were statistically analyzed, which was complemented by participant observations (Bogdan; Biklen, 2010) – enabling the collection of qualitative data. The triangulation of quantitative and qualitative data analyzed has indicated changes in the school climate, particularly from the perspective of the administration team. This change was driven by the intensification of the school monitoring policy through the digital platforms implemented by Seduc and by the changes this team underwent in the period between the administration of the pre- and post-school climate tests.
School climate in a public school participating in São Paulo state’s full-time education program
Keywords: Clima escolar; Programa Ensino Integral; Equipe Gestora.; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; 4. Educação de Qualidade